The Role of Islamic Education in Raising Legal Awareness About Online Gambling in Jambi Province - Musa, Musa; Taridi, Muhamad; Kholil, Abdul; Wahyudi, Fitrah; Kiswanto, Heri (Jurnal Educative: Journal of Educational Studies, 2024)
This study examines the role of Islamic educational institutions in Jambi Province in raising legal awareness about online gambling. The research aims to explore how Islamic education can enhance legal awareness regarding online gambling, considering its negative impacts such as financial losses, addiction, increased crime, and mental health issues. A qualitative case study approach was employed, with data collected through in-depth interviews with 6 Islamic education teachers, document analysis of curriculum materials, educational policies, lesson plans, and observations of 3 participants. The findings reveal that Islamic educational institutions in Jambi Province play a pivotal role in addressing online gambling among students through various effective methods. By integrating Islamic moral values into the curriculum, utilizing technology, and employing religious lectures and case-based learning, these institutions have successfully raised students' awareness about the effects of online gambling. Despite challenges such as initial student unawareness and curriculum constraints, collaboration among schools, pesantren, and religious communities presents opportunities to enhance these educational efforts. The use of social media and community outreach is also crucial in expanding awareness and mitigating the negative impacts of online gambling. In conclusion, this study highlights the significant role of Islamic education in safeguarding society from online gambling and advocates for the continued development of comprehensive educational programs to address this issue. Studi ini mengkaji peran lembaga pendidikan Islam di Provinsi Jambi dalam meningkatkan kesadaran hukum terhadap judi online. Penelitian ini bertujuan mengeksplorasi bagaimana pendidikan Islam dapat meningkatkan kesadaran hukum mengenai judi online, yang berdampak negatif seperti kerugian finansial, kecanduan, peningkatan kejahatan, dan gangguan kesehatan mental. Metode yang digunakan adalah pendekatan studi kasus kualitatif, dengan mengumpulkan data melalui wawancara mendalam dengan 6 pengajar agama Islam, analisis dokumen terhadap materi kurikulum, kebijakan pendidikan, rencana pelajaran, dan observasi terhadap 3 partisipan. Hasil penelitian menunjukkan bahwa lembaga pendidikan Islam di Provinsi Jambi memainkan peran kunci dalam menangani judi online melalui berbagai metode efektif. Integrasi nilai-nilai moral Islam ke dalam kurikulum, pemanfaatan teknologi, serta penggunaan ceramah agama dan pembelajaran berbasis kasus berhasil meningkatkan kesadaran siswa tentang dampak judi online. Meskipun terdapat tantangan seperti kurangnya kesadaran awal dan batasan kurikulum, kolaborasi antara sekolah, pesantren, dan komunitas religius menawarkan peluang untuk meningkatkan inisiatif ini. Penggunaan media sosial dan penyuluhan komunitas juga menjadi faktor penting dalam memperluas kesadaran dan mengatasi dampak negatif judi online. Kesimpulannya, penelitian ini menekankan pentingnya pendidikan Islam dalam melindungi masyarakat dari judi online dan mendorong pengembangan program pendidikan yang lebih komprehensif untuk mengatasi masalah tersebut.